Allestimenti partigiani: le mostre della Resistenza, 1945-1946 - Maffioletti, Serena (Lo sguardo rinnovato, 2026)
The essay aims to interpret the exhibitions held in Milan, Turin, and Genoa in 1945–1946 by anti-Fascist and partisan architects, artists, and intellectuals, who fought for liberation from Nazi-Fascism. Organized just a few weeks after 25 April 1945, installed in spaces devastated by bombing, and addressed to citizens who had grown up under Fascism and were worn down by years of war, they reveal the innovation and the political, social, and cultural energy that emerged from reflections on the value and role of art developed during the years of regime-imposed censorship and in experiments with clandestine communication. Until now the subject of studies mainly by historians of the Resistance, these exhibitions attest – through the opening of buildings of power to public use, the interaction between exhibition design, graphic design, and photography, and the collaboration between politicians and citizens – to that “leap of history” which inaugurated the trajectory of Italian exhibitions in the 1950s.